Development of Contextual Intercropping-Based Student Worksheets to Facilitate Students’ Problem-Solving Skills - Sularni Sularni; Mariana Ade Cahaya; Winda Ramadianti (Journal of Research in Social Science and Humanities, 2026)
This research was motivated by the low mathematical problem-solving ability of eighth-grade students at SMPN 15 Bengkulu Utara on the topic of linear equations and inequalities of one variable, as indicated by an average score of 40. In addition, the Student Worksheets (LKPD) used in the classroom are not contextual, less engaging, and have not optimally facilitated the development of students’ problem-solving skills. Therefore, this study aims to develop intercropping context-based LKPD that are valid and practical in facilitating students’ mathematical problem-solving abilities. This research employed a development research approach using the 4D model adapted into three stages, namely define, design, and develop. The study was conducted at SMPN 15 Bengkulu Utara. The research subjects consisted of 10 students of class VIII B in the limited trial and 23 students of class VIII A in the field trial during the 2025/2026 academic year. The research instruments included expert validation sheets as well as teacher and student response questionnaires. The collected data were analyzed using descriptive quantitative techniques through percentage calculations to determine the validity and practicality levels of the developed product.The results showed that the intercropping context-based LKPD obtained a validity percentage of 90.18% from experts, which falls into the highly valid category. Meanwhile, the practicality results indicated that the LKPD achieved a score of 93.33% based on teacher responses and 88.15% based on student responses, both categorized as highly practical. Therefore, the developed LKPD is considered valid and practical for facilitating students’ mathematical problem-solving skills.